1980
DOI: 10.1007/bf01910222
|View full text |Cite
|
Sign up to set email alerts
|

The effect of defect structure due to doping and irradiation on the thermal decomposition of potassium chlorate

Abstract: The thermal decomposition of potassium chlorate was investigated as a function of doping and there seems to be a correlation between the polarizing nature of the dopant cation and the thermal degradation temperature of potassium chlorate. In particular, transition metal cations influence strongly the temperature of decomposition. Irradiation and mechanical shock defects influence also the process. A possible mechanism in terms of the semi-conductive properties of the defective chlorates is discussed.Chlorine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is reported that sodium dichromate catalyzes the decomposition of KCIO3 (Udupa, 1981). It is also reported that when FeCls and CuCl2 were doped into KCIO3, the decomposition temperature of KCIO3 decreased significantly (Rudloff and Freeman, 1980). This may also be a catalytic effect rather than an effect of doping, because no structural changes were detected by X-ray diffraction analysis, and the chlorides have very different crystal structure from KCIO3.…”
Section: Introductionmentioning
confidence: 97%
“…It is reported that sodium dichromate catalyzes the decomposition of KCIO3 (Udupa, 1981). It is also reported that when FeCls and CuCl2 were doped into KCIO3, the decomposition temperature of KCIO3 decreased significantly (Rudloff and Freeman, 1980). This may also be a catalytic effect rather than an effect of doping, because no structural changes were detected by X-ray diffraction analysis, and the chlorides have very different crystal structure from KCIO3.…”
Section: Introductionmentioning
confidence: 97%